STRATEGI PEMASARAN DIGITAL TERINTEGRASI DALAM MENINGKATKAN VISIBILITAS DAN DAYA SAING UMKM KULINER - Lady, Lady; Jesslieca; Arief, Ronny Firdiansyah; Qadri, Rizni Aulia (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2026)
Culinary SMEs in urban areas often face low brand visibility and high dependency on local customers near their physical locations. This study aims to implement an integrated digital marketing strategy for Shan Nasi Lemak in Batam to expand its market reach. A qualitative case study method was employed through observation, documentation, and in-depth interviews. The intervention involved standardizing visual identity, optimizing Google Maps profiles, and activating creative content on Instagram, TikTok, and GrabFood platforms. The results indicate that the multichannel strategy significantly improved the business's digital performance, as evidenced by thousands of organic video views and a broader reach to new audiences beyond the initial followers. Qualitative validation confirms that improved visual aesthetics and ease of access to information enhance consumer trust and purchase intention. This research concludes that the synergy between professional visual identity and consistent digital platform management is a crucial instrument for SMEs in building sustainable competitiveness in the urban market.